DETEKSI HEPATITIS B Surface Antigen (HBsAg) DENGAN PERBANDINGAN WAKTU DAN AKURASI RAPID TEST DAN Enzyme-Linked Immunosorbent Assay (ELISA) - Nasywa Luthfi Zain; Indah Sulistiyawati; Muryanti Muryanti (Bioscientiae, 2026)
Hepatitis B is one of the serious infectious diseases that is still a global health problem. Early detection of HBsAg infection is very important to prevent further complications. This study aims to compare the detection time and accuracy between the rapid test and Enzyme-Linked Immunosorbent Assay (ELISA) in detecting HBsAg. The study used two methods, then analyzed based on age and gender variables. The rapid test showed advantages in detection speed, but had limitations in accuracy. Meanwhile, ELISA takes longer but provides more sensitive and specific results. The results of this study indicate that the selection of diagnostic methods must consider clinical needs so that the combination of both methods can increase the effectiveness of early detection and control of Hepatitis B infection in the community.